Respuesta :

MsRay

Answer:

(-2, 1)

Step-by-step explanation:

Systems of equations can be solved using different methods.  For this set of systems, you can multiply each equation by a factor in order to eliminate a variable and solve for the other variable:

-3(-5x - 3y = 7)  or 15x + 9y = -21

5(-3x - 4y = 2)  or -15x -20y = 10

                                    -11y = -11

                                        y = 1

Solve for x:  -5x - 3 = 7

Add 3 to both sides:  -5x -3 + 3 = 7 + 3 or -5x = 10

Solve for x: x = -2

(-2, 1)